Effect of viscous, viscoplastic and friction damping on the response of seismic isolated structures. - Makris, Nicos (Earthquake engineering & structural dynamics.)
In this paper the efficiency of various dissipative mechanisms to protect structures from pulse type and near source ground motions is examined. Physically realizable cycloidal pulses are introduced, and their resemblance to recorded near source ground motions is illustrated. The study uncovers the coherent component of some near source acceleration records, and the shaking potential of these records is examined. It is found that the response of structures with relatively low isolation periods is substantially affected by the high frequency fluctuations that override the long duration pulse. Therefore, the concept of seismic isolation is beneficial even for motions that contain long duration pulse which generates most of the unusually large recorded displacements and velocities. Dissipation forces of the plastic (friction) type are very efficient in reducing displacement demands although occasionally they are responsible for substantial permanent reducing displacement demands although occasionally they are responsible for substantial permanent displacements. It is found that the benefits by hysteretic dissipation are nearly indifferent to the level of the yield displacement of the hysteretic mechanism and that they depend primarily on the level of the plastic (friction) force. The study concludes that a combination of relatively low friction and viscous forces is attractive since base displacements are substantially reduced without appreciably increasing base shears and superstructure accelerations.